METHOD FOR MINERALIZING BIOPOLYMER FILMS AND FILMS OBTAINED THEREFROM - Patent application
A novel method forms biopolymer membranes with nanocrystals using an electric field to address the limitations of existing biopolymer membranes, achieving rapid resorption and biological benefits for tissue repair.
Patent Information
- Application Number
- JP2022521599
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2019-10-10
- Filing Date
- 2020-10-09
- Publication Date
- 2025-01-22
- Estimated Expiration
- 2040-10-09
AI Technical Summary
Existing biopolymer membranes used for tissue engineering and bone regeneration lack rapid resorbability and effective biological properties, such as antioxidant and anti-inflammatory effects, while conventional mineralization methods result in hard crystals that can damage tissues.
A method involving a biopolymer membrane assembly between cellulose sheets in compartments with calcium and phosphate ion solutions, subjected to an electric field to form nanocrystals with a honeycomb structure, ensuring rapid resorption and biological benefits.
The method produces biopolymer membranes with nanocrystals that are rapidly resorbed and provide antioxidant and anti-inflammatory effects, suitable for various therapeutic applications, including bone and cartilage repair, with no tissue damage.
Smart Images

Figure 0007619572000009 
Figure 0007619572000010 
Figure 0007619572000011
Abstract
Description
[Technical field]
[0001] The present invention relates to the field of tissue engineering, namely the production of synthetic biocompatible organic tissues that are implantable in living organisms.
[0002] More particularly, the present invention relates to a method for preparing a biomaterial for use in human surgery and medicine, said biomaterial consisting of a biopolymer film coated with nanocrystals of an inorganic compound, said nanocrystals having a specific structure, said biopolymer film being particularly capable of being coated with nanocrystals of a calcium phosphate compound, in particular chosen from hydroxyapatite or brushite. [Background technology]
[0003] In medicine, the implantation of biopolymer structures in living organisms is a conventional technique, which is used to promote the reconstruction of biological tissues, in particular bone tissue.
[0004] These biopolymer structures, used as bone substitutes, consist of natural fibers (in the form of films, fibers, small and / or porous structures) that are often combined with active compounds to increase their biocompatibility: cells, hormones and / or growth factors or minerals.
[0005] These bone substitutes must enable osteoconduction, which refers to the ability of a biomaterial to act as an inert support for bone regeneration. The biomaterial must also be porous and resorbable. The porosity of the biomaterial allows the implant to be vascularized and gradually resorbed. The resorption rate of the biomaterial must correspond to the needs of bone regeneration tissue formation, i.e. not too fast so that the material can act as a support for bone formation, and not too slow so as to limit the risk of infection and not impair bone growth by physical obstacles.
[0006] As inert supports for cellular and tissue colonization, several types of biomaterials have been used: they can be natural or synthetic ceramics or various materials of natural origin, whose chemical composition is close to that of the mineral phase of bone.
[0007] The majority of synthetic biomaterials, often used to fill bone defects, are two mineral species of the phosphate family, hydroxyapatite and tricalcium phosphate, either pure or in mixtures.
[0008] Combinations of biopolymers with nanocrystalline hydroxyapatite, such as collagen and hydroxyapatite, are known and have been used as bone substitutes since the 1990s (see, e.g., U.S. Pat. No. 5,231,169, U.S. Pat. No. 6,201,039, and European Patent No. 0747067).
[0009] Various therapeutic applications of this biomaterial have been proposed, including, for example: - EP 3181158 A1 relates to a nanoporous biomaterial, comprising hydroxyapatite deposited or precipitated on a gel of biodegradable polymers, in particular chosen from collagen and alginate, which may be used in dental surgery, for reconstructive surgery and in orthopedics. - WO 2008 / 096334 describes an implant intended to repair cartilage damage, which comprises a scaffold composed of collagen and hydroxyapatite. - Russian Patent Application No. 2410040 describes a prosthesis consisting of a collagen or alginate membrane covered with hydroxyapatite crystals, which is intended for the surgical treatment of female urinary incontinence. - WO 2013 / 111077 describes a composition for the treatment of gastrointestinal disorders, comprising, inter alia, sodium alginate and hydroxyapatite. WO 2013 / 190534 describes a compressible composite powder comprising a composition of silicate, collagen and calcium phosphate. The powder can be obtained by grinding a material composed of mineralized collagen and can be used as an implant. Several methods for mineralizing biopolymer films have been described so far. The conventional technique consists in firing minerals, for example ceramics, at very high temperatures, which results in very hard crystals.
[0010] The following "gentler" techniques have also been proposed: - US Patent No. 6,395,036 describes a method for preparing a composite material in which calcium and phosphate ions circulate around a collagen membrane and, when they come close to each other, deposit as hydroxyapatite crystals. - WO 2008 / 096334 describes a method for preparing a collagen scaffold covered with hydroxyapatite crystals by freeze-drying and gelling. - EP 3021883 describes a composite material comprising a scaffold of collagen fibres at least partially covered with hydroxyapatite crystals by epitaxial growth. The method for obtaining said material involves immersing the collagen fibres in an aqueous solution saturated with calcium and phosphate ions (Ca2+ / HxPO4(3-x)) to form nanocrystals of hydroxyapatite on the collagen fibres, the method being terminated by removing the collagen from the aqueous solution and washing it. - Russian Patent No. 2174848 describes a method for preparing a mineralized collagen membrane, which involves circulating ions by electrophoresis using electrodes. Under the action of this current, the calcium-containing solution oxidizes, producing hydrogen ions that can dissolve the formed hydroxyapatite crystals. The proposed solution is to stabilize the pH of the solution at 11 for the solution of calcium ions and at a value of 10.5-11 for the solution containing phosphate ions, which is done by continuously adding calcium hydroxide to the solution containing calcium ions. - US Patent No. 5,532,217 and US Patent No. 5,739,286 relate to a method for mineralizing collagen fibers, in which the collagen fibers are inserted into a vessel that comprises two tanks, one containing calcium chloride and the other potassium phosphate. The two vessels are separated by a tube made of a cellulose dialysis membrane, in which the collagen fibers are inserted. The pH of the solution is adjusted so that ions precipitate and form nanocrystals on the collagen. This procedure is relatively slow and lasts for 7 days. - US Patent No. 6,589,590 describes a method for mineralizing a biopolymer, which comprises contacting one side of a biopolymer film with a solution containing calcium ions and the other side of the biopolymer film with a solution containing phosphate ions, which diffuse through the biopolymer film and deposit as hydroxyapatite upon contact with each other.
[0011] The present invention relates to a novel method for "gentle" mineralization of biopolymer films, which involves the implementation of a unique combination of different methods to obtain mineral nanocrystals in said films. This mineralized film has interesting novel properties. In fact, the crystals formed are in a state of low crystallinity and have specific structural qualities. The mineralized film is rapidly resorbable (5-60 days, in particular less than 30 days, less than 25 days or even less than 21 days) after implantation in the organism and has favorable biological effects (antioxidant, anti-inflammatory) at the time of implantation in the organism or after administration of a powder prepared from this mineralized film.
[0012] Due to the novel properties of these mineralized biopolymer films, new therapeutic applications can be envisioned in addition to the treatment of bone and cartilage damage. Summary of the Invention
[0013] The present invention relates to a method for mineralizing a biopolymer film, the method comprising: a) An assembly (3) consisting of two cellulose sheets (A) and (B) and a biopolymer membrane (4) between them, - a first compartment (1) and a second compartment (2) each comprising an electrode, the first electrode being an anode arranged in the first compartment (1) and the second electrode being a cathode arranged in the second compartment (2); - walls of a first compartment (1) and a second compartment (2) that are in contact with each other, each having an opening through which the first compartment and the second compartment communicate with each other; introducing into a container comprising: said introducing step in which an assembly (3) is placed in the opening between the adjacent first and second compartments, with the cellulose sheet (A) on the side of the first compartment (1) and the cellulose sheet (B) on the side of the second compartment (2); b) filling the first compartment (1) with an aqueous solution containing at least one cation selected from calcium, silver, zinc, copper, sodium, magnesium and aluminium ions and filling the second compartment (2) with an aqueous solution containing at least one anion selected from fluoride, sulphate, carbonate, silicate and phosphate ions; c) applying a voltage between the electrodes; d) inverting the assembly (3) so that the cellulose sheet (A) is on the side of the second compartment and the cellulose sheet (B) is on the side of the first compartment, or exchanging the solutions and electrodes between the first and second compartments; c') applying a voltage between the electrodes, the voltage being equal to the voltage applied in step (c) and for the same duration as the voltage applied in step (c); e) removing and cleaning the assembly (3); and f) recovering and drying the mineralized biopolymer film.
[0014] The present invention also relates to a biopolymer membrane mineralized on its two faces, obtainable by the method described above.
[0015] The present invention also relates to a biopolymer membrane mineralized on its two faces with nanocrystals of calcium phosphate organized in the form of plate-shaped and spherical nanoporous crystals with a honeycomb structure.
[0016] Another subject of the invention is a powder composed of a mineralized biopolymer film, for example as described above, which is powdered.
[0017] Another subject of the invention is a solution of said powder suspended in a pharma- ceutically acceptable carrier.
[0018] The present invention also relates to a mineralized biopolymer film as described above, or a powder as described above, or a solution as described above, for its therapeutic use in the treatment of diseases of bone tissue, cartilage tissue, pancreatic tissue, kidney tissue, urethral tissue, urethral and bladder tissue, testicular tissue, ovarian tissue, intestinal tissue, liver tissue, nervous tissue, cardiac tissue, tympanic tissue, ocular tissue, urinary tissue, gynecological tissue, lung tissue, bronchial tissue, tracheal tissue, vascular tissue, connective tissue, skin tissue, mucosal tissue, dental tissue, gingival tissue and / or hematopoietic tissue, as well as immune. [Brief description of the drawings]
[0019] [Figure 1] 1 shows a cross-section of a vessel comprising a first compartment (1) and a second compartment (2), each of which comprises an electrode, an anode arranged in the first compartment (1) and a cathode arranged in the second compartment (2), and an assembly (3) placed in an opening between the first and second compartments, which are brought into close proximity, comprising a biopolymer membrane (4) surrounded by two cellulose sheets, of which cellulose sheet (A) is on the side of the first compartment (1) and cellulose sheet (B) is on the side of the second compartment during step (c). [Diagram 2] FIG. 2 represents a similar device as shown in FIG. 1, but in which during step (c') the assembly (3) is inverted so that the cellulose sheet (A) is on the side of the second compartment (2) and the cellulose sheet (B) is on the side of the first compartment (1). [Diagram 3] 3 represents the change in total antioxidant capacity measured in the urine of an individual (a healthy 67-year-old male) administered a powder according to the invention. The total antioxidant capacity (TAC) is expressed as a percentage compared to the control value as a function of the number of days of administration (X-axis). [Figure 4]Figure 4 shows photographs of the crystals present on the membrane, taken on a Zeiss Supra 55VP scanning electron microscope (SEM) on both sides of a mineralized collagen membrane. Samples 7, 4, 6 and 5 were taken at the following magnifications (from left to right): ×250, ×750, ×2000, ×10,000, ×20,000 and ×30,000. The leftmost photograph shows the appearance of the mineralized membrane without magnification. Sample 5 corresponds to the membrane obtained by the method according to the invention. [Diagram 5] FIG. 5 is a photograph of the crystals present on the film of Sample 5 taken with a Zeiss Supra 55VP scanning electron microscope (SEM) at the following magnifications: ×20,000 and ×30,000. The top is Face 1 (Face 1) and the bottom is Face 2 (Face 2). [Figure 6] Figure 6 shows the diffractograms of mineralized collagen matrices. Comparison of the diffraction spectra obtained for manually ground samples 7, 4, 6 and 5. [Figure 7] Figure 7 shows curve fits in the HPO4 region to the normalized IR spectra, comparing the bands corresponding to PO4 groups and apatitic and labile HPO4 groups in hand-ground sample 5 (top) and sample 7 (bottom). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0020] The present invention relates to a method for mineralizing a biopolymer film, which makes it possible to obtain specific types of nanocrystals on said film, which have the advantage of rapid absorption after implantation in the organism, and which have a favorable biological effect at the time of its implantation in the organism or after administration of a powder obtained from said film.
[0021] Biopolymer Membrane A membrane is a common term that refers to a flexible wall. Each membrane has a certain stiffness and porosity.
[0022] A polymer is a macromolecule composed of an assembly of several monomeric units. Biopolymers refer to natural polymers produced directly by living organisms (plants, algae, animals, fungi, etc.) or derived directly from natural products. Biopolymers are compounds based on amino acids, sugars, nucleotides, or other monomeric organic compounds. A distinction is made between biopolymers of plant origin and biopolymers of animal origin.
[0023] Among the biopolymers of plant origin, mention may be made in particular of cellulose, starch and alginates (produced by seaweed).
[0024] Among the biopolymers of animal origin, mention may be made in particular of collagen and chitosan, resulting from the processing of chitin produced by crustaceans.
[0025] According to a preferred embodiment of the invention, the biopolymer membrane is a collagen, alginate or chitosan membrane.
[0026] According to a first embodiment, the membrane is made of collagen.
[0027] Collagen is a protein polymer composed of three linked alpha polypeptide chains made up of amino acids. These chains are linked by hydrogen bonds between hydroxylysine (https: / / fr.wikipedia.org / wiki / Hydroxylysine) and hydroxyproline (https: / / fr.wikipedia.org / wiki / Hydroxyproline) and by covalent bonds. The polymer usually organizes in the form of fibers. There can be several types of linkages and organization of the polypeptide chains, i.e. there are several types of collagen, designated type I, type II, type II, etc. Collagen is present in the extracellular matrix of animal cells and provides tissues with physical resistance to stretching. Collagen is used in many therapeutic applications, as it has a very low allergenicity.
[0028] According to a second embodiment, the membrane is made of alginate.
[0029] Alginate is a polysaccharide produced by seaweed. It is a polymer formed by two monomers: mannuronate or mannuronic acid, the specific unit of which is acetylated, and guluronic acid or guluronic acid. The ratio and distribution of these two monomers varies, i.e., there are several types of alginate, which have varying chemical and physical properties. In medicine, alginate is used to encapsulate fragile drugs or biological materials. Alginate can also be used in sugar formulations of certain dressings. Alginate is also a product used by dentists to make dental impressions.
[0030] According to a third embodiment, the membrane is made of chitosan.
[0031] Chitosan is a polysaccharide composed of randomly distributed β-(1-4) linked D-glucosamine (deacetylated unit) and N-acetyl-D-glucosamine (acetylated unit). It is produced by chemical deacetylation of chitin in alkaline or enzymatic medium, a component of the exoskeleton of arthropods, the endoskeleton of cephalopods or the septum of mushrooms. Chitosan is widely used in cosmetics and food. In medicine, chitosan can be used as a biomaterial, especially for tissue regeneration, hemostasis and bone formation.
[0032] The shape of the biopolymer film shall be, for example, a parallelepiped, such as a square, a rectangle or a diamond.
[0033] The size of the biopolymer membrane will be selected by those skilled in the art depending on the envisaged application, but may be, for example, about 10 cm. 2 Or 20cm 2 Or 100cm 2 (10x10cm square) and can be of much larger dimensions, e.g. 1m 2 , 10m 2Or another 100m 2 It can also be of a size of
[0034] assembly With regard to the method of mineralizing a biopolymer membrane according to the invention, the membrane is placed inside an assembly consisting of two identical cellulose sheets, shown as (A) and (B), which distinguish the position of said sheets facing two compartments containing separate aqueous solutions.
[0035] This assembly is placed between the two compartments (1) and (2) so as to separate them air-tight, i.e. the only contact surface between the two solutions in each of these compartments (1) and (2) is the assembly.
[0036] The cellulose sheets (A) and (B) used are identical. The size of the cellulose sheet is slightly larger than that of the biopolymer membrane to ensure leak tightness between compartments (1) and (2). Its thickness is preferably between 0.02 mm and 0.03 mm. The cellulose sheet may in particular be a sheet of cellophane.
[0037] Membrane mineralization: using ionic solutions During step (b) of the method according to the invention, the first compartment and the second compartment are filled with an aqueous solution of: - in a first compartment (1), an aqueous solution containing at least one cation chosen from calcium ions, silver ions, zinc ions, copper ions, sodium ions, magnesium ions and aluminium ions, and in a second compartment (2), an aqueous solution containing at least one anion chosen from fluoride, sulfate, carbonate, silicate and phosphate ions.
[0038] For example, the following solutions may be used in the practice of the invention: [Table 1]
[0039] According to a preferred embodiment of the invention, the aqueous solution present in the first compartment (1) contains at least calcium ions and the aqueous solution present in the second compartment (2) contains at least phosphate ions.
[0040] According to another preferred embodiment of the invention, in addition to the presence of ions resulting from the decomposition of water, the aqueous solution in the first compartment (1) contains only calcium ions as cations and the aqueous solution in the second compartment (2) contains only phosphate ions as anions.
[0041] Preferably, these will be the following solutions: - calcium chloride Ca(Cl)2 with the addition of calcium hydroxide Ca(OH)2, and - Ammonium phosphates, including one, two or three solutions of substituted ammonium phosphates to which a solution of concentrated aqueous ammonia (NH3) to 25% by weight has been added.
[0042] It should be understood that these solutions may contain, apart from the ions identified above, other ions which make it possible to optimize the chemical mineralization reaction of the biopolymer film.
[0043] It may be necessary to adjust the pH of each solution, for example, by adding acid or base.
[0044] According to a preferred embodiment, the aqueous solution containing at least one anion has a pH between 7 and 11. This is in particular obtained by adding concentrated aqueous ammonia (NH3) to the aqueous solution.
[0045] According to another preferred embodiment, calcium hydroxide is added to the calcium chloride solution in order to maintain a constant concentration of calcium ions, which makes it possible to avoid excessive acidification of the calcium chloride solution.
[0046] Depending on the aqueous solution used, the skilled person will employ the addition of other compounds to the solution to maintain a particular pH and / or optimize the reaction, as necessary, for example for solutions containing zinc or silver or magnesium or aluminum ions.
[0047] Advantageously, each solution used will be protected from any contamination with the aqueous solution of the other, in order to make the reaction as efficient as possible.
[0048] According to the implementation of the method of the invention, each solution is injected into each of the compartments (1) and (2) after installation of the assembly (3), in a manner that avoids any contamination.
[0049] Apparatus: container and electrodes 1 and 2 show schematic representations of an apparatus suitable for carrying out the method of the present invention, designated as an "electrophoresis tank", which includes a vessel and electrodes.
[0050] The apparatus comprises a first compartment (1) and a second compartment (2) each comprising an electrode, which for carrying out step (c) of the method is an anode disposed in the first compartment (1) and a cathode disposed in the second compartment (2).
[0051] The anode is defined as the attracting electrode for negative ions (anions) that is exposed to the electric field during the electrolysis process. It may be made, for example, of carbon or graphite fibers. The connecting element may advantageously be made of gold or platinum.
[0052] The cathode is defined as the attracting electrode for positive ions (cations) that is exposed to an electric field during the electrolysis process. It can be made of steel, for example.
[0053] The device may be constructed of any type of solid inert material, such as glass, plastic, or plexiglass.
[0054] Advantageously, each compartment has an independent exhaust system, which makes it easier to carry out step (d) of exchanging solutions and electrodes between the two compartments.
[0055] The device also comprises an opening in each of the walls of the first compartment (1) and the second compartment (2) that are in contact with each other, said openings allowing communication between the first and second compartments.
[0056] These openings, also denoted "windows", will have a size appropriate to the size of the biopolymer membrane (4). They may for example have a surface area of 10 cm x 10 cm or 15 cm x 15 cm.
[0057] According to a preferred embodiment of the invention, the device comprises a stirrer, in particular immersed in the solution in compartment (1) containing at least one cation, in order to continuously homogenize said solution.
[0058] Step (c) and Step (c'): Applying a voltage between the electrodes In these two steps, a voltage (direct current) is applied between the two electrodes by a generator.
[0059] Preferably, its intensity is adjusted to obtain a real voltage of 2 to 13 volts or 3 to 13 volts, better still 5 to 12 volts or 7 to 10 volts.
[0060] This actual voltage is the same during the two steps (c) and (c') and is applied for equal duration during the two steps, which allows to obtain the same level of mineralization on each side of the biopolymer film.
[0061] Note that during this step the voltage will fluctuate, i.e. with respect to the programmed current intensity, the voltage will naturally tend to drop when the conductivity is correct, and at the end of this process the intensity will also drop, as the formed nanocrystals slow down the passage of the current.
[0062] This voltage is applied during steps (c) and (c') for a duration of 8 to 16 hours, preferably about 12 hours.
[0063] The effect of this voltage is to cause the ions to migrate in the solution surrounding the assembly and, after passing through the cellulose sheets (A) and (B), to deposit on the side of the biopolymer film that is not in the solution containing the cations, forming nanocrystals.
[0064] Preferably, during steps (c) and (c'), the aqueous solution containing at least one cation is continuously stirred to maintain a basic pH and to remove H + The decomposition of the crystals caused by the generation of ions is avoided.
[0065] Preferably, during steps (c) and (c'), the aqueous solution containing at least one cation is saturated with said cation by continuously adding the hydroxide of said cation, which allows the pH of the solution containing calcium ions to be maintained at a value close to 11 and in addition allows constant reconstitution of the cation. The advantages of this embodiment are described in patent RU 2174848.
[0066] Step (d): Inverting the biopolymer film Step (d) of allowing the other face of the membrane to mineralize can be carried out according to two different variants: 1) the assembly (3) constituted by the biopolymer membrane and the cellulose sheet is removed through the opening between the two compartments and is inverted so that sheet (A) is now in contact with the aqueous solution of the second compartment and sheet (B) is in contact with the aqueous solution of the first compartment, of course taking all precautions to avoid contamination of each solution with ions from the other solution; 2) or carrying out an exchange of solutions and electrodes between the first and second compartments, i.e. for carrying out step (c') as described above, the cathode is in the first compartment (1), in a solution containing at least one anion, and the anode is in the second compartment (2), in a solution containing at least one cation.
[0067] According to a first embodiment of the method according to the invention, step (d) is as follows: inverting the assembly (3) so that the cellulose sheet (A) is on the side of the second compartment and the cellulose sheet (B) is on the side of the first compartment.
[0068] According to a second embodiment of the method according to the invention, step (d) consists in: exchanging the solution and the electrodes between the first and second compartments.
[0069] The final steps (e) and (f) of the method At the end of step (c'), the voltage is turned off and the assembly (3) is removed and then washed with water. The cellulose sheets (A) and (B) are removed and discarded.
[0070] The two-sided mineralized biopolymer film is dried by any technique known to those of skill in the art.
[0071] Advantageously, the step (f) of drying the mineralized biopolymer film is carried out at a temperature below 35°C.
[0072] Preferably, the drying step lasts for 12 to 24 hours.
[0073] Mineralized biopolymer membrane One of the subjects of the present invention is a biopolymer membrane mineralized on its two faces, obtainable by the method as described in the present application.
[0074] Another subject of the invention is a biopolymer membrane mineralized on its two faces, obtained by the method described in this application.
[0075] This biopolymer film is characterized by containing on its two faces nanocrystals organized in the form of plate-shaped and spherical nanoporous crystals with a honeycomb structure.
[0076] These nanocrystals may in particular be composed of the following inorganic compounds: calcium phosphate compounds, in particular chosen from: Hydroxyapatite and / or ○ Defective hydroxyapatite doped with fluoride ions, silver ions or zinc ions, and / or Polysubstituted apatite or defective hydroxy-, fluoro- or carboxy-apatite, and / or Brushite (calcium hydrogen phosphate dihydrate: CaHPO4.2H2O) and / or Calcium phosphate compounds containing unstable hydrogen phosphate groups, - Magnesium sulfate, or - Aluminum sulfate, or - Any combination of these inorganic compounds.
[0077] The deposition of ions on the biopolymer film leads to the formation of nanocrystals, defined as crystals with a size of the order of nanometers (of the order of 43-45 nm). These nanocrystals then form aggregates of micrometer size.
[0078] According to a particular embodiment, this membrane is covered on both sides by nanocrystals of calcium phosphate, also denoted nanocrystals of calcium phosphate compounds.
[0079] According to one aspect of the invention, the mineralized biopolymer film has two faces each of which is represented by the general formula Me 10 It is coated with apatite nanocrystals of the formula (XO4)6Y2, where Me represents a divalent cation, XO4 represents a trivalent anionic group, and Y represents a monovalent anion.
[0080] The apatite structure can accommodate a number of substitutions: divalent cations (Me 2+ ) is a divalent cation (Mg 2+ , Ag 2+ , Zn 2+ , Sr 2+ , B.A. 2+ , Pb 2+ ), but also by monovalent (e.g. Na + , K + ) or trivalent (La 3+ , Ga 3+ ,EU 3+ ) cations. Similarly, the trivalent anion XO4 3- is divalent (CO3 2- , SO4 2- , HPO4 2- ), trivalent (AsO4 3- , VO4 3- ) or tetravalent (SiO4 4- Finally, the Y-group may also be substituted by monovalent (F-, Cl-) or divalent (CO3 2- , O 2- , S 2- ) ions.
[0081] According to the method of the invention, all possible combinations of cations and anions can be envisaged, depending on the solutions used during the implementation of the method.
[0082] The following table 2, extracted from the paper by Antoine BOYER entitled "Synthesis, Characterisation et Evaluation Biologique d'Apatites Phosphocalciques Carbo-Silicates" (Synthesis, Characterisation and Biological Evaluation of Carbonate-Silicate Substituted Calcium Phosphate Apatites), presents different types of apatites of biological interest that can be obtained by the method according to the invention.
[0083] [Table 2]
[0084] From a biological point of view, magnesium is of interest due to its role in bone remodeling at the moment of mineralization. Silver has antibacterial properties. Strontium has been identified in the mineralized tissue of bone and seems to play an important role in its mineralization. Zinc has an inhibitory effect on osteoclast activity in vitro.
[0085] Regarding anion substitution, the presence of fluoride ions F- determines bone growth. In its absence, bone densification is limited, whereas too high concentrations can lead to osteosclerosis. Cl- ions have the ability to create an acidic environment on the bone surface, which activates osteoclasts in the resorption process to solubilize alkaline salts of bone minerals.
[0086] Thus, incorporation of such ions into the apatite structure can alter and potentially improve the biological activity of the mineralized biopolymer film.
[0087] According to a particular embodiment of the invention, the mineralized biopolymer film is often labeled with Ca to emphasize that the lattice of the crystal structure has two molecules. 10 It is coated on two faces with hydroxyapatite nanocrystals of the general formula Ca5(PO4)3(OH), written as (PO4)6(OH)2.
[0088] This so-called "stoichiometric" hydroxyapatite contains 39% Ca, 18.5% P and 3.38% OH, the percentages being expressed as weight of the mineral / total weight. Hydroxyapatite is the major mineral component of tooth enamel, dentin and bone. The CAS number for hydroxyapatite is 12167-74-7.
[0089] According to another particular embodiment of the invention, the mineralized biopolymer film is coated on two sides with nanocrystals of brushite (calcium hydrogen phosphate dihydrate, general formula CaHPO4.2H2O) and nanocrystals of calcium-deficient carbonated hydroxyapatite.
[0090] The mineralized membrane according to the invention has a number of advantages, in particular the very rapid resorption capacity of the hydroxyapatite after introduction into the body.
[0091] The mineralized membrane according to the invention can advantageously be completely absorbed in a time period between 5 and 60 days after implantation in the living body. The membrane according to the invention can be absorbed in less than 10 days, less than 15 days, less than 20 days, less than 25 days, less than 30 days, less than 40 days, less than 50 days or less than 60 days after implantation in a living body, in particular a human or an animal.
[0092] These absorption times were measured in several animal models (rabbits, rats, dogs) as presented in Example 6. It should be noted that in most cases the film or powder is absorbed in less than 25 days, but for certain therapeutic applications, such as nerve regeneration, it may be necessary to wait up to 60 days before complete absorption is observed.
[0093] The membranes according to the invention are non-tumorigenic, non-toxic, non-immunogenic and completely biocompatible due to their high ability to biointegrate in the recipient organism, avoiding rejection or encapsulation of the membrane.
[0094] The present invention also relates to a biopolymer membrane mineralized on its two faces with nanocrystals of inorganic compounds organized in the form of spherical nanoporous crystals with plate-shaped and honeycomb structures.
[0095] These inorganic compounds may be one of those mentioned above and may in particular be chosen from: calcium phosphate compounds, in particular chosen from: Hydroxyapatite and / or ○ Defective hydroxyapatite doped with fluoride ions, silver ions or zinc ions, and / or Polysubstituted apatite or defective hydroxy-, fluoro- or carboxy-apatite, and / or Brushite (calcium hydrogen phosphate dihydrate: CaHPO4.2H2O) and / or Calcium phosphate compounds containing unstable hydrogen phosphate groups, - Magnesium sulfate, or - Aluminum sulfate, or - Any combination of these inorganic compounds.
[0096] The invention particularly relates to a biopolymer membrane mineralized on its two faces with calcium phosphate nanocrystals organized in the form of plate-shaped and spherical nanoporous crystals with a honeycomb structure.
[0097] Example 7 of the present application shows structural properties of this membrane that have not been observed until now: in particular, the organization of the nanocrystals in the form of spherical nanoporous crystals with plate-like and honeycomb structures is not observed in the control sample, which has coarse aggregates and an inhomogeneous structure.
[0098] This structure of nanocrystals deposited on the film according to the invention is particularly advantageous for the following reasons: - the plate shape does not contain "needle-like" structures that tend to damage the tissue of the body into which the membrane is to be introduced; - The spherical crystals with a honeycomb structure, after implantation in the body, make it possible to fix biological proteins circulating around the membrane, which take an active role in the healing and absorption of the implanted material.
[0099] According to a particular embodiment, the biopolymer that constitutes the membrane is collagen.
[0100] The present invention also relates to a biopolymer membrane mineralized on two of its faces with nanocrystals of an inorganic compound, in particular calcium phosphate, organized in the form of spherical nanoporous crystals with a plate-like and honeycomb structure, obtainable or obtainable by the method of the present invention.
[0101] Another subject of the present invention is the following specific pharmaceutical formulation of one of these mineralized biopolymer films. a powder consisting of one of these biopolymer films, powdered by any means selected by the person skilled in the art, or otherwise; - A solution of said powder suspended in a pharma- ceutically acceptable carrier.
[0102] Pharmaceutically acceptable carriers refer to carriers or excipients, i.e., compounds that have no inherent action on the body. These carriers or excipients are pharma- ceutically acceptable, meaning that they can be administered to the body without causing significant adverse effects.
[0103] Thus, according to the invention, the powder obtained contains nanocrystals, for example of biopolymers as defined previously, and in particular of hydroxyapatite, the nanocrystals being in particular organized in the form of spherical nanoporous crystals with a platelet shape and a honeycomb structure.
[0104] therapeutic use The mineralized membranes may be introduced into living organisms, particularly humans, to repair defects in bone, cartilage, or other structural organs.
[0105] The mineralized membrane powder, or a solution containing it, may be administered to an individual by any form of administration known to those skilled in the art, in particular by oral, sublingual, inhalation, subcutaneous, intramuscular, intravenous, transdermal, ocular, or rectal routes.
[0106] That is, the present invention relates to the biopolymer films, or powders, or solutions as described above, and their therapeutic uses in the treatment of disorders of bone tissue, cartilage tissue, pancreatic tissue, kidney tissue, urethral tissue, urethral and bladder tissue, testicular tissue, ovarian tissue, intestinal tissue, liver tissue, nervous tissue, cardiac tissue, tympanic tissue, ocular tissue, urinary tissue, gynecological tissue, lung tissue, bronchial tissue, tracheal tissue, vascular tissue, connective tissue, skin tissue, mucosal tissue, dental tissue, gingival tissue and / or hematopoietic tissue, as well as immune.
[0107] In particular, the present invention relates to biopolymer films, or powders, or solutions, such as those described above, and to their therapeutic use in the treatment of pancreatic disorders.
[0108] In particular, the present invention relates to biopolymer films, or powders, or solutions, such as those described above, and their therapeutic use in the treatment of kidney disease.
[0109] In particular, the present invention relates to biopolymer films, or powders, or solutions, such as those described above, and to their therapeutic use in the treatment of urological disorders.
[0110] In particular, the present invention relates to biopolymer films, or powders, or solutions, such as those described above, and their therapeutic use in the treatment of dental diseases.
[0111] In particular, the present invention relates to biopolymer films, or powders, or solutions, such as those described above, and their therapeutic use in the treatment of gynecological disorders.
[0112] In particular, the present invention relates to biopolymer films, or powders, or solutions, such as those described above, and their therapeutic use in the treatment of hematopoietic and immune disorders.
[0113] In particular, the present invention relates to biopolymer films, or powders, or solutions, such as those described above, and to their therapeutic use in the treatment of inflammation.
[0114] In particular, the present invention relates to biopolymer films, or powders, or solutions, such as those described above, and their therapeutic use in the treatment of diseases associated with high oxidative potential.
[0115] The present invention also relates to a method of treatment for the treatment of disorders of bone tissue, cartilage tissue, pancreatic tissue, renal tissue, urethral tissue, urethral and bladder tissue, testicular tissue, ovarian tissue, intestinal tissue, hepatic tissue, nervous tissue, cardiac tissue, tympanic tissue, ocular tissue, urinary tissue, gynecological tissue, pulmonary tissue, bronchial tissue, tracheal tissue, vascular tissue, connective tissue, skin tissue, mucosal tissue, dental tissue, gingival tissue and / or hematopoietic tissue, and immune in a human, comprising administering to said human an effective amount of a mineralized biopolymer film, powder or solution as described herein.
[0116] The present invention also relates to a dietary supplement comprising a powder or solution as described above.
[0117] The powder or solution according to the invention, in addition to simply acting in the case of inflammation, injury or disease, has its activity limited over time by its effective amount. This powder or solution does not lead to the phenomenon of unregulated or uncontrolled cell replication. It has no effect on undamaged cell division, i.e. it is not a growth factor.
[0118] Mineralized biopolymer membranes are used in surgery as Class 3 "DMI" materials during surgical interventions on the body. - Alone and dry, or -- It can be used in conjunction with antibiotics (C3G, vancomycin, gentamicin, etc.) or with regenerative hormones (oxytocin, serotonin, etc.). -
[0119] It can also be used in the form of a "plate" for implantation or surface deposition in contact with the organ. It is not necessary to use plates of a specific shape, the regeneration of the organ is self-organizing.
[0120] Tissue regeneration will be initiated in situ at the time of resorption of the material under physiological conditions after surgery by inflammatory mediators and host cells (M1 and M2 macrophages, differentiated cells and stem cells). - The mineralized biopolymer membrane, when in the form of an injectable powder (reconstituted in physiological serum or xylocaine), can be used in: -- bone marrow (local or systemic use), -- Joints, -- soft tissue (e.g. in the nasal septum to regenerate septal defects) or mesotherapy, -- Eye drops or intravitreal injections, -- Ear drops or nose drops, -- solutions into capillaries or onto the skin, -- absorbable collagen or chitosan tubes connecting the nerve endings, or --Venous (stimulates angiogenesis following tissue regeneration phenomena).
[0121] The powder may also be administered by spraying onto: - Bronchi and lungs, or - The nose (due to the cerebral pathways), or - On the skin (either as a powder alone or in specific cream formulations). EXAMPLES
[0122] Example 1: Method for mineralizing a collagen membrane In this embodiment, 100 cm 2 A collagen membrane of size (10×10) is mineralized on both sides with hydroxyapatite nanocrystals according to the protocol described below.
[0123] The vessel used is made of glass. Its window (the communicating opening between the two compartments) is 10 x 10 cm.
[0124] 1- Preparation of Solutions The two solutions of calcium chloride and ammonium phosphate were prepared by completely dissolving the powders in a beaker using a dedicated pipette, and 2 x 2.5 liters of - Ammonium phosphates (including solutions of one, two or three of the substituted ammonium phosphates (NH4H2PO4, (NH4)2HPO4, (NH4)3PO4)); and - Calcium chloride with subsequent addition of Ca(OH)2, get.
[0125] 2- Preparation of the "sandwich" (assembly (3)) A cellulose sheet is placed on each side of the collagen membrane.
[0126] 3-Filling the tank: This requires that each side fill at the same rate so the liquids do not mix, to avoid the pressure in the fully filled compartment distorting the assembly.
[0127] PO4 3- A few drops of concentrated aqueous NH3 solution are added to the compartment containing the ions.
[0128] Ca ++ Sodium hydroxide solution is added to the compartment containing the ions.
[0129] 4-Installation of electrodes and stirrer The negative electrode (cathode) is made of steel and is immersed in an ammonium phosphate bath.
[0130] The anode is made of solid graphite (carbon) or graphite (carbon structure) and is connected to a Ca ++ Immerse in bath.
[0131] 5- How to Start A direct current is applied to the electrodes so that the actual voltage is between 2 volts and 13 volts.
[0132] The method is carried out at room temperature for a total of 24 hours, with the electrodes and solution being inverted after 12 hours.
[0133] 6-End of procedure Gently stop the stir bar and electrophoresis. Remove the electrodes to avoid contaminating the solution.
[0134] The collagen membrane incorporating the hydroxyapatite nanocrystals is removed and dried at a temperature not exceeding 30-35°C (approximately room temperature) for approximately 12-24 hours.
[0135] Example 2: Effects observed upon administration of the product according to the invention The favorable effects of the administration of these products according to the invention have been observed in the following tissues: -- Bone tissue (treatment of bone matrix loss and nonunion, treatment of osteomyelitis) -- Cartilage tissue (hyaline and articular) (regeneration of cartilage) -- Renal tissue (hemostasis and incision reinforcement for partial renal resection) -- Liver tissue (filling of liver cysts, post-hepatectomy, hemostasis, guiding liver regeneration) -- Nerve tissue (regeneration of peripheral nerve dehiscences) -- Cardiac tissue (revascularization and myocardial regeneration after a heart attack) -- Tympanic tissue, ocular tissue (regeneration of the tympanic membrane, treatment of congenital glaucoma) -- Urological tissue (e.g., to guide the healing of hypospadias) -- Gynecologic tissue (endovascular treatment of female infertility, cervical regeneration) -- Lung tissue (filling of cysts or parenchymal losses, reinforcing bronchial sutures) -- Connective and supporting tissues (stress urinary incontinence) -- Skin and mucosal tissues (wounds, ulcers, gingivopathy, etc.), and -- Dentistry (treatment of caries, tooth implantation and preparation, bone formation before implants).
[0136] Example 3: Specific use in intramedullary bone injections: Distant action The "powder" form can be reconstituted in an injection solution (e.g., 1 ml of dry powder diluted in 2-4 ml of vital serum and / or 1% xylocaine), which can then be injected into the bone marrow, for example at the iliac crest, using a syringe and bone trocar.
[0137] The effects occurring at the site of hematopoietic and immune tissues will lead to a decrease in the inflammatory response.
[0138] For example, after postoperative injection into the iliac crest, improvement and reduction of inflammation at the incision surface of a liver resection can be observed.
[0139] Administration of the powder in suspension has a favorable effect at the location of the damaged area of the myocardium after injection into the iliac crest after onset.
[0140] Example 4: Oral and buccal use as a dietary supplement Plates and powders can be administered orally and are absorbed through the buccal and gingival mucosa.
[0141] It is administered twice daily for 30 days. The observed effects are as follows: - locally, the improvement of the trophic function of the gingival tissue, restoring the tension of the dental ligaments during tooth movement; - Systemically, there was improvement in mood and general symptoms due to reduction in joint pain and arthropathy at the 5th day of intake.
[0142] In individuals with type 2 diabetes, favorable effects on glycemic control were observed following twice-daily administration of a powder according to the invention.
[0143] Example 5: Antioxidant activity of the products after oral administration measured in urine Oral intake of a powder according to the invention in the morning and evening by an individual steadily increased the total antioxidant capacity measured in urine samples, as shown in FIG.
[0144] TAC (Total Antioxidant Capacity) is a biological marker that measures the antioxidant power of body fluids. The person skilled in the art knows the various test methods used to measure TAC, and good correlations have been found between the results obtained by the various techniques. Urine samples are collected in a non-invasive manner that is of considerable interest in testing the antioxidant status of the body.
[0145] The study protocol is summarized below: Three participants in good general health were enrolled in the study: two men aged 67 and 75 years and one woman aged 25 years. Figure 3 shows the results obtained in the 67-year-old man, but similar results were obtained in the other two individuals tested.
[0146] Early morning urine control samples were obtained fasting at 7 hours, followed by 8 and 19 hours following the regular protocol.
[0147] Measurement of the total antioxidant capacity of the samples was carried out by conventional coulometric analysis, which measures the amount of electricity consumed or produced during electrolysis.
[0148] The results were expressed as a percentage compared to a control sample, and rutin, a flavonoid with recognized antioxidant properties, was used as a "standard." Urine samples were assayed for total antioxidant capacity, values of which were 100% at 1 dm 3 This is equivalent to 285 to 1647 mg of rutin (Ru) per liter.
[0149] FIG. 3 shows a clear increase in the total antioxidant capacity of urine taken from a patient taking a powder according to the invention twice a day, from the first few days (up to day 6, where the capacity measured is "oxidative" and not antioxidant) to days 10-12, when the percentage of antioxidant capacity in the urine samples is high.
[0150] Example 6: Absorption of the membranes obtained by the method according to the invention in different animal models (rat, rabbit, dog) The resorption of the membrane is determined by histological analysis after implantation into specific tissues in animals (rats, rabbits or dogs) and subsequent biopsy of the implanted area at various time points.
[0151] The observed resorption is rapid and progressive loss of the implanted material occurs gradually in the microvasculature (angiogenesis), in the connective tissue and then in the functional tissue of cell formation.
[0152] Specific experiments carried out on the subcutaneous tissue of dogs and rabbits on the absorption time of mineralized membranes in the form of plates or powders showed the following: - Day 2 (D2)-Day 3 (D3) post-implantation (pi): Partial resorption of the mineralized membrane in the presence of a high proportion of eosinophilic granulocytes. Swelling of collagen fibers. - Day 5 (D5) to day 7 (D7) pi: Considerable resorption of the mineralized membrane in the presence of multinucleated giant cells, lymphocytes and macrophages. - Day 14 pi (D14): A high percentage of mononuclear cells within some islands with a mineralized membrane remaining. In place of the absorbed complexes, there is young mature granulation tissue with blood vessels formed by typical squamous endothelial cells filled with blood cells. The transition of the granulation tissue to fibrous tissue is also noted. - Day 25 pi (D25): In place of the lost membrane, separate islands of fully developed mature connective tissue are seen, surrounded by macrophages, multinucleated giant cells, and lymphocytes. The membrane is not rejected. The morphological changes in the membrane implant area correspond to an intense cellular proliferative response due to replacement of the collagen-apatite complex with fibrous connective tissue.
[0153] Tables 3 to 8 below show the histological development observed depending on the host cell and the time after implantation (pi: post implantation).
[0154] [Table 3]
[0155] [Table 4]
[0156] [Table 5]
[0157] [Table 6]
[0158] [Table 7]
[0159] Table 8. Treatment of peripheral nerve transection in rats (rats, n=5)
[0160] A loss of 1 cm of nerve material was observed in the sciatic nerve. A solution consisting of a powder made by crushing mineralized membrane was placed in a keratin tube connecting both ends of the disrupted nerve.
[0161] Clinical findings are recorded in Table 8 below. [Table 8]
[0162] Example 7: Molecular characterization of calcium phosphate crystals present on the membrane obtained by the method according to the invention Calcium phosphate nanocrystals obtained by several different mineralization methods were compared as follows: - Sample 7: No cellophane - collagen membrane mineralized for 24 hours without electrophoresis - Sample 4: Collagen membrane mineralized for 24 hours with cellophane and without electrophoresis - Sample 6: Collagen membrane mineralized for 24 hours without cellophane and with electrophoresis - Sample 5: collagen membrane mineralized for 24 hours with cellophane-with electrophoresis, i.e. according to the method of the invention.
[0163] The samples were analyzed by the following characterization techniques: Zeiss Supra 55VP Scanning Electron Microscope (SEM) Observations were performed at low voltage without any conductive surface deposition and without masking the morphology of aggregates and calcium phosphate crystals formed on the surfaces of collagen fibers. Bruker D8 Advance 9 / 9 XRD X-ray diffractometer (XRD) equipped with a Lynx-Eye position sensitive detector (opening angle 2.946°) with CuKα radiation (40 kV and 40 mA). The diffractograms were analyzed using TOPAS-64 V6 software. A VERTEX 70 infrared (IR) spectrometer (Bruker Optics, France) equipped with an attenuated total reflectance system (Quest ATR Diamond; Specac, USA). To be able to compare the spectra with each other, controls were added and a "curve fitting" procedure was performed, following the procedure developed by Baptiste Charbonnier in his paper (EMSE, 09 / 12 / 2016).
[0164] A- Analysis by electron microscope observation 4 and 5 show images obtained by scanning electron microscopy (SEM) on both sides of the mineralized collagen membrane at several magnifications.
[0165] The image shows: - Sample 7, obtained without a porous cellophane membrane and without electrophoresis, is very thick, highly mineralized, fairly dense, and blocked / occluded on Face 1 (magnification ≥ ×10,000). Electron microscopically, the mineralized matrix 7 resembles flakes of gypsum. The morphology of the surface aggregates is rough on both sides of the membrane at low magnification. A relatively heterogeneous morphology of the CaP crystals appears between the two sides of the membrane at higher magnification (≥ ×10,000). - Sample 4, obtained with a porous cellophane membrane and without electrophoresis, is very thin and very poorly mineralized, unlike sample 7. On Face 1, the collagen matrix is clearly visible (yellow in the picture). The mineral layer on this face is very thin but very dense, and the pores seem to be completely closed / occluded. Mineral globules with a diameter ≦1 μm are randomly visible on this face (Face(1)), while they are absent on the other face (Face(2)). The differences between Face 1 and Face 2 are clear. - Sample 6, obtained without a porous cellophane membrane and with electrophoresis, was relatively thick, like Sample 7, but with a clear variation in thickness (up to 100%, photo of Sample 6). The mineral formed on each side of the collagen membrane (i.e. Faces 1 and 2) was relatively more porous than in Sample 7, with one side (Face 1) being rough, with randomly distributed aggregates (diameter of about 10 μm) and a non-uniform nanostructure, and the other side (Face 2) being composed of mineral globules with a diameter of ≦1 μm. The concentration of these globules was clearly higher than for Face 1 of Sample 4. - Sample 5, obtained with a porous cellophane membrane and with electrophoresis, is significantly different from the other three samples, whether on the membrane scale, the aggregate scale, or the nanometer scale.
[0166] Under an electron microscope, the membrane has the same appearance on both sides (photo, sample 5). Both sides have small, shiny crystals and the mineral thickness and color are relatively uniform.
[0167] The crystals visible in the SEM images are calcium phosphate plates / sheets, i.e. "leaflet-shaped", that are very characteristic of the brushite phase (CaHPO4,2H2O). The plates are relatively large, up to 100 μm or more in length, and relatively thin, <1 μm thick (grown along fairly precise crystallographic planes). The surface is irregular in shape and relatively porous.
[0168] This shape is the result of the aggregation of crystals in the form of plates and spherical nanoporous crystals, the latter with submicron pores of around 10 μm in diameter, similar to the holes in a honeycomb. The walls of these pores, i.e. the crystals, are extremely thin, on the order of nanometers.
[0169] FIG. 5 shows images taken by scanning electron microscopy on both sides of the membrane at magnifications (Mag) ×20,000 and ×30,000.
[0170] This morphology of the nanocrystals is very unique and very interesting. In fact, the size and shape of the holes allows the capture of biological proteins of interest (for example growth or healing factors such as BMP2). The thin walls with the shape of the honeycomb holes significantly increase the exchange surface with the fluids, i.e. the interaction capacity of these nanocrystals with the fluids.
[0171] In conclusion, the method of mineralizing collagen membranes according to the present invention, involving a porous membrane (cellophane type) and an electric field, effectively produces not only unique and oriented crystal morphology, but also a uniform distribution of these crystals on each side of the membrane.
[0172] B-Diffractogram of manually crushed mineralized membrane FIG. 6 shows a comparison of the diffraction spectra obtained on milled films of samples 7, 4, 6 and 5.
[0173] All samples have spectra with relatively broad and not very intense diffraction peaks.
[0174] Samples 7 and 4, obtained without electrophoresis, have a single and unique detectable crystalline phase, the crystallographic structure of which is close to that of hydroxyapatite (marked PDF file 09-0432).
[0175] Samples 6 and 5 obtained with electrophoresis have two crystalline phases, one whose crystallographic structure is closer to that of hydroxyapatite (HA, PDF09-0432) and the other one that is clearly closer to that of brushite (PDF09-0077).The diffraction peaks are also narrower than those of the apatite structure compared to brushite, suggesting that the local order of brushite is higher than that of the apatite crystals.
[0176] These results, together with those presented above, confirm that the plate-shaped bodies observed by SEM of sample 5 (method according to the invention) are relatively well crystallized brushite crystals growing along very precise crystallographic planes, and that the submicroscopic porous spheres are crystals with a crystallographic structure close to that of hydroxyapatite (HA).
[0177] C-Normalized infrared (IR) spectra acquired on manually ground mineralized membranes The results confirm that sample 4, produced with a porous cellophane membrane and without electrophoresis, is less mineralized than the other samples.
[0178] Samples 7 and 6 obtained without a cellophane membrane showed that the phosphate group (1200–900 cm -1 , 620~480cm -1 ), hydroxyl group (3500cm -1 , 620cm -1 ), and carbonate groups (1700-1200cm -1 , 910~830cm -1 ), i.e., the samples consist essentially of defective carbonate hydroxyapatite of the general formula: Ca10-x(PO4)6-x.(HPO4 2- or CO3 2- )x.(OH or 1 / 2CO3)2-x, where 0≦x≦2.
[0179] These samples also showed a labile HPO group at 542 cm -1(e.g., lower graph of FIG. 7) This band is assigned to either the outside of the apatite structure or to HPO4 ions trapped within the brushite.
[0180] Similarly, sample 5 produced with a porous cellophane membrane and under electrophoresis has bands for apatite groups and also bands for unstable HPO4 groups (e.g., upper graph in FIG. 7). However, the bands for apatite are less intense than those observed in the spectrum of sample 7, while the bands at 542 cm for unstable HPO4 groups are not. -1 The bands at 0.05 and 0.15 are of higher intensity. These semi-quantitative results confirm the previous SEM and DRX findings.
[0181] Sample 7 also appears to be more mineralized than sample 5 (Figure 7, 560 cm -1 Phosphate band at / 510cm -1 The results also confirm the visual findings by SEM and the density and blocked / occluded appearance of the surface of the samples taken without electrophoresis.
[0182] In conclusion, the method of the present invention of performing controlled mineralization of porous cellophane membranes and porous organic membranes by electric fields effectively allows to obtain a relatively homogeneous mineral density within the organic membrane as well as a unique morphology and mineral composition of CaP crystals. The morphological features of calcium-deficient carbonated hydroxyapatite crystals, highly oriented and shaped like honeycomb holes, are of particular interest for biological applications (e.g. trapping proteins in submicron pores, very high exchange surface / crystal weight ratio).
[0183] References European Patent No. 3181158 International Publication No. 2008 / 096334 Russian Patent Application No. 2410040 International Publication No. 2013 / 111077 International Publication No. 2013 / 190534 U.S. Patent No. 6,395,036 International Publication No. 2008 / 096334 European Patent No. 3021883 Russian Patent Application No. 2174848 U.S. Patent No. 5,532,217 U.S. Patent No. 5,739,286 U.S. Patent No. 6,589,590
[0184] A paper by Antoine BOYER entitled "SYNTHESE, CARACTERISATION ET EVALUATION BIOLOGIQUE D'APATITES PHOSPHOCALCIQUES CARBO-SILICATEES" discussed in Saint-Etienne on April 17, 2014.
Claims
1. 1. A method for mineralizing a biopolymer film, comprising: a) an assembly (3) consisting of two cellulose sheets (A) and a biopolymer membrane (4) between the cellulose sheets (B), a first compartment (1) and a second compartment (2) each comprising an electrode, said first electrode being an anode arranged in said first compartment (1) and a second electrode being a cathode arranged in said second compartment (2); - walls of the first compartment (1) and the second compartment (2) that are in contact with each other, each having an opening through which the first and second compartments communicate with each other; introducing into a container comprising: said introducing step in which an assembly (3) is placed in said opening between the first and second compartments brought closer together, with the cellulose sheet (A) on the side of the first compartment (1) and the cellulose sheet (B) on the side of the second compartment (2); b) filling the first compartment (1) with an aqueous solution containing at least one cation selected from calcium, silver, zinc, copper, sodium, magnesium and aluminium ions and filling the second compartment (2) with an aqueous solution containing at least one anion selected from fluoride, sulphate, carbonate, silicate and phosphate ions; c) applying a voltage between the electrodes; d) turning the assembly (3) over so that the cellulose sheet (A) is in the second compartment and the cellulose sheet (B) is in the first compartment, or exchanging solutions and electrodes between the first and second compartments; c') applying a voltage between the electrodes, the voltage being equal to the voltage applied in step (c) and for a period of time equal to the voltage applied in step (c); e) removing and cleaning said assembly (3); f) recovering and drying the mineralized biopolymer film. Law.
2. The method of claim 1 , wherein the biopolymer membrane is a collagen, alginate, or chitosan membrane.
3. 3. The method according to any one of claims 1 to 2, characterized in that the aqueous solution present in the first compartment (1) contains at least calcium ions and the aqueous solution present in the second compartment (2) contains at least phosphate ions.
4. 4. The method according to claim 1, wherein during steps (c) and (c'), the voltage applied is between 2 and 13 volts.
5. 5. The method according to claim 1, wherein the application of the voltage in step (c) lasts for 8 to 16 hours.
6. 6. The method according to claim 1, wherein during steps (c) and (c'), the aqueous solution containing at least one cation is continuously stirred.
7. 7. The method according to claim 1, characterized in that, between steps (c) and (c'), the aqueous solution containing at least one cation is saturated with said cation by continuously adding a hydroxide of said cation.
8. 8. The method according to claim 1, wherein the pH of the aqueous solution containing at least one anion is between 7 and 11.
9. 9. The method according to any one of claims 1 to 8, characterized in that the drying of the mineralized biopolymer film of step (f) is carried out at a temperature below 35°C, preferably for a period of 12 to 24 hours.
10. A biopolymer film, mineralized on two sides by nanocrystals of an inorganic compound, organized by the aggregation of plate-shaped crystals and spherical nanoporous crystals having a honeycomb structure, obtained by the method described in any one of claims 1 to 9.
11. The membrane of claim 10, wherein the biopolymer is collagen.
12. 12. The membrane according to claim 10 or 11, characterized in that the nanocrystals are constituted by calcium phosphate.
13. A powder consisting of a mineralized biopolymer film according to any one of claims 10 to 12, powdered.
14. 14. A solution comprising the powder of claim 13 suspended in a pharma- ceutically acceptable carrier.
15. 15. A mineralized biopolymer film according to any one of claims 10 to 12, or a powder according to claim 13, or a solution according to claim 14, for therapeutic use in the treatment of diseases of bone tissue, cartilage tissue, pancreatic tissue, kidney tissue, urethral tissue, urethral and bladder tissue, testicular tissue, ovarian tissue, intestinal tissue, liver tissue, nervous tissue, cardiac tissue, tympanic tissue, ocular tissue, urinary tissue, gynecological tissue, lung tissue, bronchial tissue, tracheal tissue, vascular tissue, connective tissue, skin tissue, mucosal tissue, dental tissue, gingival tissue and / or hematopoietic tissue and immune.
Citation Information
Patent Citations
Method for producing complex of gel support and hydroxyapatite
JP2009209313A
Method of manufacturing organic-inorganic hybrid disk and structure used for its method
JP2009261582A
Method for forming bone tissue on the calcium phosphate (hydroxyapatite) base
RU2174848C1
Method of surgical treatment of stress urinary incontinence in women
RU2410040C1
Process for the mineralization of collagen fibers, product produced thereby and use thereof to repair bone
US5532217A